Estudio de prefactibilidad para la instalación de un sistema de quioscos universitarios, con pago mediante aplicación móvil y tarjetas de tecnología sin contacto - Terán Samanamud, Omar Enrique (2019)
The present project consists in the implementation of a kiosk, integrated with the current technology; which will have as main purpose to streamline the flow of purchases and a personalized interaction with the customer, by means of a pre-loaded card of the kiosk, via mobile application and without leaving the traditional channel with physical money.